Buriti: um framework para apoiar a tomada de decisão a partir de dados educacionais públicos na Educação Básica - Doglas Wendll Sorgatto (2024)
Basic Education is the period of compulsory education for Brazilian citizens between the ages of 4 and 17, and the knowledge acquired in its three stages (early childhood education, elementary education, and high school) has an impact on the lives of students and society as a whole. Therefore, the analysis of available data on basic education, especially those related to the quality of this education, can provide important information to support decision-making. To this end, we used public education data and other databases to analyze some stages of national education in search of patterns, anomalies and trends. To achieve this, the Buriti framework was created, inspired by learning analytics, dimensional data modeling reference models, and a framework to support decision-making in education. Buriti was used in this work to analyze SAEB performance data, in its national values, comparatively by Federation Unit, specifically for the State of Mato Grosso do Sul and for a group of schools. These analyses, carried out in five case studies, showed that there are performance problems in basic education that cause an involution in learning, especially between the 5th and 9th grade, which are not resolved in high school and have an impact on the entry of students to higher education. It is also conveyed that there is a strong relationship between performance in SAEB and socioeconomic level, a weaker relationship between performance in SAEB and teacher training. Thus, this work has contributed to the identification of problems in basic education, the creation of Buriti and the expansion of the application of learning analytics processes.